Infant mortality trends in a region of Belarus, 1980–2000 - Lawvere Silvana; Mahoney Martin C; Zichittella Lauren J; Michalek Arthur M; Chunikhovskiy Sergey P; Khotianov Natan (BMC Pediatrics, 2004)
Abstract Background The Chernobyl disaster in 1986 and the breakup of the former Soviet Union (FSU) in 1991 challenged the public health infrastructure in the former Soviet republic of Belarus. Because infant mortality is regarded as a sensitive measure of the overall health of a population, patterns of neonatal and postneonatal deaths were examined within the Mogilev region of Belarus between 1980 and 2000. Methods Employing administrative death files, this study utilized a regional cohort design that included all infant deaths occurring among persons residing within the Mogilev oblast of Belarus between 1980 and 2000. Patterns of death and death rates were examined across 3 intervals: 1980–1985 (pre-Chernobyl), 1986–1991 (post-Chernobyl & pre-FSU breakup), and 1992–2000 (post-Chernobyl & post-FSU breakup). Results Annual infant mortality rates declined during the 1980s, increased during the early 1990s, and have remained stable thereafter. While infant mortality rates in Mogilev have decreased since the period 1980–1985 among both males and females, this decrement appears due to decreases in postneonatal mortality. Rates of postneonatal mortality in Mogilev have decreased since the period 1980–1985 among both males and females. Analyses of trends for infant mortality and neonatal mortality demonstrated continuous decreases between 1990, followed by a bell-shaped excess in the 1990's. Compared to rates of infant mortality for other countries, rates in the Mogilev region are generally higher than rates for the United States, but lower than rates in Russia. During the 1990s, rates for both neonatal and postneonatal mortality in Mogilev were two times the comparable rates for East and West Germany. Conclusions While neonatal mortality rates in Mogilev have remained stable, rates for postneonatal mortality have decreased among both males and females during the period examined. Infant mortality rates in the Mogilev region of Belarus remain elevated compared to rates for other western countries, but lower than rates in Russia. The public health infrastructure might attempt to assure that prenatal, maternal, and postnatal care is maximized.